Gagasan Resiprokal Dalam Poligami; Telaah Pemikiran Abdul Halim Muhammad Abu Syuqqah - Faidol Mubarok (Fakultas Syariah IAIN Madura, 2022)
This paper discusses polygamy as a form of marriage in terms of the reciprocal concept of Abdul Halim Muhammad Abū Syuqqah. This research is focused on answering Abū Syuqqah's reciprocal ideas about polygamy and Abū Syuqqah's reciprocal ideas. The researcher concludes that Abū Syuqqah's idea of ​​reciprocity is based on three schemes, namely through text, context, and contextuality which are interconnected using a reciprocal approach which intends that the text reciprocally applies to all parties in gender relations. Abū Syuqqah is of the opinion that reciprocal polygamy is obligatory based on considerations for the good of all family members, both husband, wife and children. Through this method also, Abū Syuqqah stipulates the conditions for polygamy, namely the husband's ability to be fair to his wives and children, the ability to provide a living for all family members, and the ability to look after and educate his wife and children.